A translation of some chapters in "Basic accounting". - Đinh Thị Hạnh.; Nguyễn Quang Thái.; Trần Đình Nguyên (Da Nang, 1999)
Theoretical background of the research; The original text; the translated texts; ...
Includes bibliography.
Keywords: English language; Translation; Account; English language -- Translation